Multi-scale patterns formed by sodium sulphate in a drying droplet of gelatin: experiment and simulation in 2-dimensions. (22nd May 2018) - Dutta, Tapati; Tarafdar, Sujata; Khatun, Tajkera
Abstract: We present a study of patterns, formed in drying drops of aqueous gelatin solution containing sodium sulphate. The patterns are highly complex, consisting of a hierarchical sequence of rings which form concentric bands as well as dendritic crystalline aggregates. We try to explain the origin of the rings and the dendritic growth from them, from a simple physical approach using the advection diffusion equations. We implement a finite difference scheme in 2-dimensions to simulate the experimental results. The effect on pattern formation using different solutions are examined by variation of contact angle and diffusivity. Our model can explain the growth dynamics of a complex pattern that covers several length scales, from the nano scale of single crystals, to the micro scale of dendrites and finally rings that are of the scale of centimeters.